From Guild to Society: The Foundation of Confrerie Pictura in The Hague Revisited - Bakker, Piet (Early Modern Low Countries, 2019)
The foundation of the Confrerie Pictura (an artistic brotherhood) in The Hague has given rise to controversy on several occasions. In the eighteenth century, for example, Johan van Gool was annoyed by Houbraken, who believed that the artist painters of The Hague had founded their Confrerie in 1662, while it was abundantly clear to Van Gool that the correct date was 1656. Nowadays the question under discussion is the nature of the Confrerie as an organisation. Was it the first step towards an eighteenth-century society, as Hoogewerff suggested in his authoritative book on the Dutch St Luke’s guilds, or was the new organisation more like a guild, as later argued by Hoogewerff’s most important critic Hessel Miedema? Based on archival records, this article maps out the early history and establishment of the Confrerie in order to determine what kind of organisation it had been between 1656 and 1700. This article argues that all four authors are right: the Confrerie was both a guild and a society, and however paradoxical it may sound, it was founded in 1656 and again in 1662.